An In Situ Depot for Continuous Evolution of Gaseous H2 Mediated by a Magnesium Passivation/Activation Cycle for Treating Osteoarthritis. (6th July 2018) - Wan, Wei‐Lin; Lin, Yu‐Jung; Shih, Po‐Chien; Bow, Yu‐Ru; Cui, Qinghua; Chang, Yen; Chia, Wei‐Tso; Sung, Hsing‐Wen
Abstract: Inflammation is involved in many human pathologies, including osteoarthritis (OA). Hydrogen (H2 ) is known to have anti‐inflammatory effects; however, the bioavailability of directly administered H2 gas is typically poor. Herein, a local delivery system that can provide a high therapeutic concentration of gaseous H2 at inflamed tissues is proposed. The delivery system comprises poly(lactic‐co‐glycolic acid) microparticles that contain magnesium powder (Mg@PLGA MPs). Mg@PLGA MPs that are intra‐muscularly injected close to the OA knee in a mouse model can act as an in situ depot that can evolve gaseous H2 continuously, mediated by the cycle of passivation/activation of Mg in body fluids, at a concentration that exceeds its therapeutic threshold. The analytical data that are obtained in the biochemical and histological studies indicate that the proposed Mg@PLGA MPs can effectively mitigate tissue inflammation and prevent cartilage from destruction, arresting the progression of OA changes.